Optimization of lentiviral delivery of barcoded anti-CD20 chimeric antigen receptors into rhesus macaque and human natural killer cells - Taha B. Hayal; Aman A. Mulla; David S.J. Allan; Brynn B. Duncan; Saanika Joshi; So Gun Hong; Rafet Basar; Katayoun Rezvani; Richard W. Childs; Chuanfeng Wu; Cynthia E. Dunbar (Molecular Therapy: Methods & Clinical Development)
Natural killer (NK) cells are pivotal in immunosurveillance and hold great potential for immunotherapy due to their ability to target malignant cells. Their low risk of causing graft-versus-host disease (GvHD) post-allogenic transplantation underscores their potential as an off-the shelf cellular therapy tool. Advances in genetic engineering focus on improving NK targeting, persistence, and fitness. However, NK cells pose challenges for lentiviral transduction, which are clinically relevant and safe. In this study, we identified Poloxamer 407 (P407) as a novel transduction enhancer for rhesus macaque (RM) and human NK cells. We found that P407 significantly improved transduction efficiency, achieving up to 60% in expanded RM NK cells, without compromising cell viability or functionality. Additionally, P407 facilitated the expression of anti-CD20 chimeric antigen receptors (CARs) with or without interleukin (IL)-15. In a xenograft mouse model, CAR-IL15 NK cells demonstrated superior anti-tumor activity, and maintained higher clonal diversity tracked by genetic barcoding compared to CAR-NK cells lacking IL-15 in vivo. Additionally, in human NK cells, P407 combined with the TBK1/IKKε inhibitor, BX795, further improved lentivirus-mediated transduction. This study is the first to engineer NK cells from a clinically relevant rhesus macaque model in an adaptive cell therapy context and highlights P407’s potential as a transduction enhancer.